Peningkatan Kemampuan Guru Bimbingan dan Konseling Dalam Memahami Kesehatan Mental Siswa - Nugraheni Warih Utami; Carolina Ligya Radjah (Universitas Negeri Malang, 2023)
Abstract: Increasing the understanding of Guidance and Counseling teachers regarding student mental health through training activities. The aim of this community service is to increase the knowledge and understanding of Malang City Guidance and Counseling teachers in understanding the mental health of junior high school students. The methods used include various lectures, discussions, educational cinema and biblioeducation. The training was carried out in 2 stages, namely stage 1 regarding the nature and importance of understanding mental health for guidance and counseling teachers and stage 2 regarding guidance and counseling media for teaching mental health. In the final activity, a satisfaction survey was carried out for the training participants. The training carried out can increase the understanding and knowledge of guidance and counseling teachers in understanding the importance of knowing students' mental health and designing guidance and counseling services that can improve students' mental health. Abstrak: Peningkatan pemahaman guru Bimbingan dan Konseling mengenai kesehatan mental siswa melalui kegiatan pelatihan Tujuan pengabdian kepada masyarakat ini adalah untuk meningkatkan pengetahuan dan pemahaman guru Bimbingan dan Konseling di MGBK Kota Malang dalam memahami kesehatan mental siswa SMP. Metode yang dipergunakan berupa ceramah bervariasi, diskusi, sinema edukasi dan biblioedukasi. Pelatihan dilaksanakan dengan 2 tahap yaitu tahap 1 mengenai hakekat dan pentingnya memahami kesehatan mental bagi guru BK dan tahap 2 mengenai media BK untuk mengajarkan kesehatan mental. Pada kegiatan akhir dilaksanakan survey kepuasan kepada peserta pelatihan. Pelatihan yang dilaksanakan dapat meningkatkan pemahaman dan pengetahuan guru bimbingan dan konseling dalam memahami pentingnya mengetahui kesehatan mental siswa dan merancang layanan bimbingan konseling yang dapat meningkatkan kesehatan mental siswa.